PENERAPAN PEMBELAJARAN DARING, MANAJEMEN WAKTU, DAN ORIENTASI MASA DEPAN TERHADAP PROKRASTINASI AKADEMIK MAHASISWA PERGURUAN TINGGI SWASTA DI BANJARNEGARA - Ratna Suryani; Yenny Purbandari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
Delaying the completion of lecture assignments is a unique phenomenon for students from year to year in every college. No exception also happened in Banjarnegara. Students are required to attend lectures and complete assigned assignments on time. Students as carriers of change in the future, have big expectations and responsibilities to be able to graduate on time by managing time as well as possible. Through online learning during the Covid-19 pandemic, lecture assignments demand completion on time and with better understanding. This study aims to determine the effect of the application of online learning, time management, and future orientation on the academic procrastination of students in Banjarnegara. This research was conducted at three colleges in Banjarnegara, with a sample of 90 respondents. The data analysis technique in this study used multiple linear regression with the help of SPSS software. Hypothesis testing using t statistical test using a significance level of 0.05 (α = 5%) to test the effect of online learning, time management, and future orientation of students on academic procrastination. The results showed that online learning had an effect on student academic procrastination, time management had no effect on student academic procrastination, while future orientation had a negative effect on student academic procrastination. Taken together, online learning, time management, and future orientation have an effect on student academic procrastination by 79%.